Psychometric properties of revised version of the fertility adjustment scale in infertile couples undergoing assisted reproductive technology. (December 2019) - Torabi, Marjan; Kazemi, Ashraf; Abdishahshahani, Mahshid
Abstract: Objective: The aim of this study is to validate the edited version of FAS for the purpose of couples undergoing ART. Study design: In this cross-sectional study, the validity of the revised version of the FAS questionnaire was assessed by testing it on 212 couples volunteered to undergo ART. The revised version comprises 12 items from the original FAS version and 6 items added based on a survey interview conducted on infertile couples. Following an assessment of the content validity and reliability, the construct validity was measured following exploratory factor analysis with a varimax rotation. The correlation of the revised fertility adjustment (R-FAS) score with the level of depression, too, was assessed using depression scale of the depression, anxiety and stress scale (DASS-21). Results: The assessment of content validity yielded a content validity index and content validity ratio of 0.75 and 0.89. The reliability of the questionnaire measured twice with a correlation index of 0.76 was confirmed. Cronbach's Alpha for the entire questionnaire was 0.83. The exploratory factor analysis was conducted on 15 items by extracting 12 items using two factors: mental freedom and acceptance of extraction conditions. The score made on the R-FAS questionnaire was correlated with the level of depression (r = 0.51; p < 0.0001). Conclusion: The study results were indicative of the validity and reliability of the questionnaire for measurement of the adjustment attributed to the infertility in couples undergoing ART. It is proposed that the infertility-related adjustment in couples undergoing ART and with a high potential for mental disorders be measured using this questionnaire.